Investigation of ATP-mediated interleukin-1 secretion in human decidua - Liu, Yaqiong (2018)
Introduction The maternal immune system plays a significant role in pregnancy maintenance. Infections during pregnancy could stimulate inflammatory responses and lead to adverse pregnancy outcomes. Interleukin-1 (IL-1), a vital pro-inflammatory cytokine, is implicated in pregnancy infection and infection-induced preterm labour. Meanwhile, human decidua, situated between the fetus and myometrium, has been hypothesized as the main source of cytokines in the presence of infection. Moreover, the most studied inflammasome–NLRP3 inflammasome, involved in the canonical IL-1β secretory pathway, has been found participating in normal pregnancy and pregnancy disorders. However, knowledge about how decidua is involved in the immune response is still limited. In this study, we investigated how IL-1β release with stimuli to TLR4 and the purinergic P2X7 receptor in the full-term decidua, especially on the key components of the inflammasome pathway.